2023
DOI: 10.1038/s41591-022-02115-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular residual disease and efficacy of adjuvant chemotherapy in patients with colorectal cancer

Abstract: Despite standard-of-care treatment, more than 30% of patients with resectable colorectal cancer (CRC) relapse. Circulating tumor DNA (ctDNA) analysis may enable postsurgical risk stratification and adjuvant chemotherapy (ACT) treatment decision-making. We report results from GALAXY, which is an observational arm of the ongoing CIRCULATE-Japan study (UMIN000039205) that analyzed presurgical and postsurgical ctDNA in patients with stage II–IV resectable CRC (n = 1,039). In this cohort, with a median follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 22 publications
(28 reference statements)
5
79
0
1
Order By: Relevance
“…Based on the results of the present study and previous work published by others, Mo and colleagues proposed potential clinical scenarios in which ColonAiQ could help guide the management of patients with localized CRC. Such clinical scenarios include adjuvant treatment escalation or intensification in molecular residual disease-positive patients and de-escalation of treatment in those patients with undetectable molecular residual disease after surgery with curative intention.…”
mentioning
confidence: 54%
“…Based on the results of the present study and previous work published by others, Mo and colleagues proposed potential clinical scenarios in which ColonAiQ could help guide the management of patients with localized CRC. Such clinical scenarios include adjuvant treatment escalation or intensification in molecular residual disease-positive patients and de-escalation of treatment in those patients with undetectable molecular residual disease after surgery with curative intention.…”
mentioning
confidence: 54%
“…Meanwhile, circulating tumor DNA (ctDNA) is an emerging biomarker that has gained popularity nowadays. ctDNA can be a prognostic and predictive biomarker in gastrointestinal cancers ( 26 28 ). Recently, Kotani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, circulating tumor DNA (ctDNA) is an emerging biomarker that has gained popularity nowadays. ctDNA can be a prognostic and predictive biomarker in gastrointestinal cancers (26)(27)(28). Recently, Kotani et al have reported results from GALAXY, which is an observational arm of the ongoing CIRCULATE-Japan study (UMIN000039205) that analyzed preoperative and postoperative ctDNA in patients with stage II-IV resectable colorectal cancer (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CGP, cfDNA analysis has been applied for the early diagnosis and detection of MRD in other types of cancer [27]. However, the barrier to clinical application in these areas is high in prostate cancer, because prostatespecific antigen (PSA), a remarkably sensitive and inexpensive biomarker, is already available.…”
Section: Difficulty Of Detecting Copy Number Lossmentioning
confidence: 99%